Genome-wide linkage mapping of Fusarium head blight resistance in common wheat (Triticum aestivum L.) - Gao, Fengmei; Zhao, Yuanling; Wang, Wei; Wang, Xiangyu; Wang, Fan; Shang, Jiawei; Qin, Bo; Wang, Yuechao; Yan, Guorong; Li, Zhongjing; Sun, Dan; Sun, Lianfa (Frontiers in Plant Science, 2025)
IntroductionFusarium head blight (FHB), caused by Fusarium graminearum, is one of the most destructive wheat diseases worldwide. FHB infection can dramatically reduce grain yield and quality due to mycotoxins contamination. Synthetic hexaploid wheat (SHW) represents a novel source of FHB resistance derived from Aegilops tauschii and Triticum turgidum that can be transferred into common wheat. Introducing new resistant germplasm, identifying loci for FHB resistance and developing available markers are crucial for wheat breeding. MethodsIn this study, a recombinant inbred lines (RIL) population originated from SHW line PS5/V975 and Sumai 3 cross were evaluated across four environments. Both the RILs and parents were genotyped using the wheat 50K single-nucleotide polymorphism (SNP) array. ResultsIn total, QFhb.haas-2DL, QFhb.haas-3BS and QFhb.haas-3BL for FHB resistance were identified and each explaining 6.2-6.8%, 7.9-9.2% and 7.6-10.4% of the phenotypic variances (PVEs), respectively. Among these, QFhb.haas-3BS was overlapped with Fhb1, QFhb.haas-2DL nearly with a resistance locus identified from CJ9306, whereas the QFhb.haas-3BL maybe novel. The favorable alleles of QFhb.haas-2DL and QFhb.haas-3BL were contributed by PS5/V975, whereas the favorable alleles of QFhb.haas-3BS originated from Sumai 3. Two kompetitive allele-specific PCR (KASP) markers, Kasp_FhbR_2DL (QFhb.haas-2DL) and Kasp_FhbR_3BL (QFhb.haas-3BL), were developed and validated in 108 common wheat accessions. Four candidate genes were selected, primarily involved in plant hormone metabolism, general metabolism, and immune response. This study provides new loci and available KASP markers in accelerating wheat breeding for higher FHB resistance. Furthermore, these results indicated that the utilization of SHW lines in breeding would introduce new sources of resistance against FHB into the common wheat gene pool.